"But it worked for my mother's cat". Some common misconceptions about anecdotal evidence. Issue 8 (3rd August 2017) - van Veggel, Nieky
Abstract: As evidence-based veterinary nursing is becoming a more common concept in veterinary practice, RVNs will more often be presented with anecdotal evidence by owners presenting to their practice. It is important that RVNs understand some of the issues associated with anecdotal and testimonial evidence and why these are not a suitable basis for decisions, so that they make decisions based on the best-available evidence and can attempt to educate clients. This article explains some of the issues surrounding anecdotal and testimonial evidence to support RVNs in their quest to practice based on evidence.